Fluvial aggradation and incision in the Brazilian tropical semi-arid: Climate-controlled landscape evolution of the São Francisco River - Mescolotti, Patricia Colombo [UNESP]; Pupim, Fabiano do Nascimento; Ladeira, Francisco Sérgio Bernardes; Sawakuchi, André Oliveira; Santa Catharina, Amanda; Assine, Mario Luis [UNESP] (Elsevier, 2021)
Large rivers are dynamic systems whose evolution depends on both internal and external forcing, particularly tectonics, sea level, and climate. Associating fluvial responses to a specific driver is a complex task that has been debated for a long time. Thus, rivers that flow exclusively under tectonically stable areas and without direct influence of relative sea level changes are suitable targets to understand how large fluvial systems responded to past climate changes. The São Francisco River is one of the largest cratonic rivers across South America, and its late Quaternary sedimentary deposits record the fluvial landscape evolution in a thousand-year timescale. The São Francisco River flows northward over different climate zones, with its upper course in a semi-humid setting, but with most of its watershed under semi-arid conditions. To understand the controls on sediment erosion, transport, and storage from uplands to lowlands, we investigated a 200-km section of the medium course of the São Francisco River in northeast Brazil. Several geomorphological zones were characterized, mapped, and dated by optically stimulated luminescence (OSL). Two zones are represented by degraded terraces with lakes, but no preserved alluvial features: (zone 1) high-level terrace (87.7 ± 12.7 ka) and (zone 2) low-level terrace (65.5 ± 5.3 to 39.3 ± 4.3 ka). Three zones comprise the active confined aggradational plain, with features such as scroll bars and abandoned channels: (zone 3) older meander belt (18.1 ± 1.6 ka); (zone 4) young meander belt (15.5 ± 1.5 to 9.5 ± 1.0 ka), and (zone 5) modern channel belt (0.4 ± 0.1 to 0.3 ± 0.1 ka). Zone 6 comprises an eolian dune field composed of parabolic dunes with two phases of active sedimentation (45.1 ± 5.2 to 25.5 ± 4.4 ka and 14.3 ± 2.6 to 5.2 ± 1.4 ka). Sediment deposition ages allowed the recognition of at least four phases of fluvial aggradation (⁓90 ka; ⁓66 to 39 ka; ⁓18 to 9 ka and ⁓0.3 ka to recent), three phases of incision (⁓85 to 66 ka; ⁓39 to 18 ka and ⁓9 to 1 ka), and two phases of dune field stabilization (⁓25 to 15 ka and ⁓5 ka to recent). Development of the eolian dune fields occurred during drier conditions, when the inland activity of trade winds reworked sediments deposited on the fluvial plain. We interpret the incision events as having been set in motion by an increase of fluvial discharge in the upper catchment area, produced by rainfall intensification due to activity of the South Atlantic Convergence Zone (SACZ). The aggradation and incision phases on the São Francisco River during the last 100 ka are therefore likely controlled by multi-millennial precipitation changes, possibly related to precession cycles. The events of high sedimentation rate in the São Francisco river mouth are partially correlated with incision phases in its middle course. This suggests that sedimentation in plains of large plateau rivers can be decoupled from the coastal area.
Keywords: Fluvial response; Fluvio-eolian interaction; Late quaternary; OSL dating; Precession cycles